Efficacy of metformin treatment in polycystic ovary syndrome: Učinkovitost zdravljenja sindroma policističnih jajčnikov z metforminom - Jerenec, Katja; Samojlenko, Maša; Geršak, Ksenija; Ferk, Polonca (Acta Medico-Biotechnica, 2021)
Metformin is an oral antidiabetic drug with potentially beneficial effects in patients with polycystic ovary syndrome (PCOS). Different pharmacological responses to met- formin have been reported in PCOS patients, which may be attributable to various clinical, biochemical, genetic and other factors. Here, we have outlined a short review of the results from current clinical studies on metformin efficacy in PCOS patients. Additionally, preliminary results from a retrospective pharmacogenetic study by our group on a sample of Slovene PCOS patients are presented. Pharmacogenetics is an emerging science that should pro- vide options for individualized medicine, the future of healthcare.
Keywords: polycystic ovary syndrome; metformin; pharmacogenetics; personalized medicine